2012
DOI: 10.1100/2012/816903
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Determinants of Nonattendance in a Population-Based Mammography Screening Program in the City of Manisa, Turkey

Abstract: Objectives. Community based breast cancer screening has decreased breast cancer mortality in women. This study examined the predictors of nonattendence for invitational breast cancer screening in relation to socioeconomic status in the city of Manisa, in western Turkey.Study Design. For the evaluation of the reasons for refusing to participate in the study, two districts were selected. 446 women aged between 50 and 69 years were selected from the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
2
13
0
6
Order By: Relevance
“…The study also showed that more than three quarters (78%) of all participants lived in Wrocław, probably because large urban centers tend to provide better access to healthcare resources. This observation is consistent with the findings of many previous studies conducted both in Poland and abroad [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study also showed that more than three quarters (78%) of all participants lived in Wrocław, probably because large urban centers tend to provide better access to healthcare resources. This observation is consistent with the findings of many previous studies conducted both in Poland and abroad [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 93%
“…Studies conducted in various countries have shown that health behaviors depend on a number of social and demographic factors, such as age, education, marital status, family situation, social class, and material conditions [17][18][19][20][21]. This article focuses specifically on the age, education, occupational status, and place of residence of screening participants under study.…”
Section: Methodsmentioning
confidence: 99%
“…Entretanto, a falta de solicitação do exame pode ser um dos problemas do rastreamento oportunístico, cuja realização necessita da solicitação da busca da mulher pelos serviços. O medo referente ao exame pode estar tanto relacionado a um diagnóstico do câncer de mama, quanto ao exame ser doloroso, motivos que também são conside-rados barreiras para a sua realização 42 . E quanto ao achar desnecessário mostra principalmente a falta de conhecimento sobre a detecção precoce do câncer de mama 43 .…”
Section: Discussionunclassified
“…Segundo a literatura 18,42 , o diálogo pode ajudar a vencer dificuldades, como a falta de solicitação médica, aliviando possíveis medos e ansiedades e informando sobre a importância da realização do exame, e consequentemente aumentando a adesão ao exame.…”
Section: Discussionunclassified
“…Although without considerable association, the fact of residing in the interior of the state contributes, albeit subtly, to less adhesion to the mammographic examination. Research has shown that the origin of the woman and the domains of CHBMS are associated (27) .…”
Section: Discussionmentioning
confidence: 99%